PENERAPAN MODEL PEMBELAJARAN INQUIRY UNTUK MENINGKATKAN KEMAMPUAN MENGIDENTIFIKASI UNSUR-UNSUR INTRINSIK PUISI BARU SISWA KELAS VIII - Pasrah Eli Hulu; Noibe Halawa; Riana; Mastawati Ndururu (Jurnal Bastra (Bahasa dan Sastra), 2025)
This classroom action research aimed to improve the ability of eighth-grade students at SMP Negeri 1 Alasa in identifying intrinsic elements of modern poetry through the application of the Inquiry learning model. The study was conducted in two cycles, each consisting of planning, action, observation, and reflection. Data were collected through observation, tests, field notes, and documentation, and analyzed both quantitatively and qualitatively. The findings revealed a significant improvement in students’ performance. In the first cycle, the students’ average score was only 57.52, with most students categorized as “poor.” After revisions in the second cycle, the average score increased significantly to 89.22, with the majority reaching the “very good” category. Students also showed greater enthusiasm, activeness, and creativity in identifying themes, diction, imagery, figures of speech, rhyme, and messages in poetry. The results indicate that the Inquiry model is not only effective in enhancing cognitive skills but also in fostering students’ motivation, participation, and creativity. Therefore, Inquiry can be considered an effective instructional model for teaching Indonesian language and literature, particularly in the development of poetry appreciation and analysis skills